Exosomes and Atherogenesis - Lin, Bingbing; Yang, Juan; Song, Yuwei; Dang, Guohui; Feng, Juan (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction and ischemic stroke are the leading causes of mortality worldwide. Atherosclerosis is their common pathological foundation. It is known that atherosclerosis is characterized by endothelial activation/injury, accumulation of inflammatory immune cells and lipid-rich foam cells, followed by the development of atherosclerotic plaque. Either from arterial vessel wall or blood circulation, endothelial cells, smooth muscle cells, macrophages, T-lymphocytes, B-lymphocytes, foam cells, and platelets have been considered to contribute to the pathogenesis of atherosclerosis. Exosomes, as natural nano-carriers and intercellular messengers, play a significant role in modulation of cell-to-cell communication. Under physiological or pathological conditions, exosomes can deliver their cargos including donor cell-specific proteins, lipids, and nucleic acids to target cells, which in turn affect the function of the target cells. In this review, we will describe the pathophysiological significance of various exosomes derived from different cell types associated with atherosclerosis, and the potential applications of exosome in clinical diagnosis and treatment.